Aport do spółki prawa handlowego a podstawa opodatkowania w podatku od towarów i usług - Pankiewicz, Paweł (Kwartalnik Prawa Podatkowego, 2015)
Contribution other than enterprise or organized part of enterprise to a commercial partnership or company is in principle a taxable event in VAT. In order to settle tax on such a legal transaction, a proper determination of taxable base is of pivotal importance. However, due to lack of detailed regulations, in this particular matter there are numerous interpretative divergences. The aim of this article is to discuss the existing approaches as regards determination of VAT taxable basis on contributions to commercial partnerships and companies together with assessment as which of them should be deemed correct in light of VAT regulations, its key construction rules stemming from the EU law as well as of theses from court verdicts, tax rulings and the tax law doctrine.